2019
DOI: 10.4236/msa.2019.103021
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Kinetics of Aluminum Powders in a Gas Fluidized Bed Reactor in the Potential Application of Surge Arresting Materials

Abstract: In this technical paper, the oxidation mechanism and kinetics of aluminum powders are discussed in great details. The potential applications of spherical aluminum powders after oxidation to be part of the surging arresting materials are discussed. Theoretical calculations of oxidation of spherical aluminum powders in a typical gas fluidization bed are demonstrated. Computer software written by the author is used to carry out the basic calculations of important parameters of a gas fluidization bed at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The polystyrene attenuation coefficient was determined from the formula present in Reference (Takagi et al 2007 ) and by using the values reported by some of us and by other authors (Spigarelli et al 2020 ; Tiong et al 2017 ; Lei et al 2013 ). In the calculation of the air acoustic impedance, the speed of sound in the air and the air density have been taken respectively from the work of Dhiren M Joshi and Shih (Shih and Shih 2019 ; Joshi n.d. ) Parameter Value Description 0.890 [mPa·s] Water dynamic viscosity (Snehota et al 2020 ) 2.485 [mPa·s] Water bulk viscosity (Snehota et al 2020 ) 998 [Kg·m −3 ] Water density (Snehota et al 2020 ) α 0.108 [cm −1 ] Polystyrene attenuation coefficient (Spigarelli et al 2020 ), X Z ps 2.5·10 6 [Pa·s·m −1 ] Polysterene acoustic impedance (Snehota et al 2020 ) Z air 4.017·10 2 [Pa·s·m −1 ] Air acoustic impedance (Racca et al 2020 ; Garino et al 2019 ) r 7.950 [mm] Well basis radius H 10.78 [mm] Solution height L D, 0.30 9.95 [nm] Bottom wall displacement at I input = 0.30 W/cm 2 L D, 0.45 12.19 [nm] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polystyrene attenuation coefficient was determined from the formula present in Reference (Takagi et al 2007 ) and by using the values reported by some of us and by other authors (Spigarelli et al 2020 ; Tiong et al 2017 ; Lei et al 2013 ). In the calculation of the air acoustic impedance, the speed of sound in the air and the air density have been taken respectively from the work of Dhiren M Joshi and Shih (Shih and Shih 2019 ; Joshi n.d. ) Parameter Value Description 0.890 [mPa·s] Water dynamic viscosity (Snehota et al 2020 ) 2.485 [mPa·s] Water bulk viscosity (Snehota et al 2020 ) 998 [Kg·m −3 ] Water density (Snehota et al 2020 ) α 0.108 [cm −1 ] Polystyrene attenuation coefficient (Spigarelli et al 2020 ), X Z ps 2.5·10 6 [Pa·s·m −1 ] Polysterene acoustic impedance (Snehota et al 2020 ) Z air 4.017·10 2 [Pa·s·m −1 ] Air acoustic impedance (Racca et al 2020 ; Garino et al 2019 ) r 7.950 [mm] Well basis radius H 10.78 [mm] Solution height L D, 0.30 9.95 [nm] Bottom wall displacement at I input = 0.30 W/cm 2 L D, 0.45 12.19 [nm] …”
Section: Methodsmentioning
confidence: 99%
“…The polystyrene attenuation coefficient was determined from the formula present in Reference (Takagi et al 2007) and by using the values reported by some of us and by other authors (Spigarelli et al 2020;Tiong et al 2017;Lei et al 2013). In the calculation of the air acoustic impedance, the speed of sound in the air and the air density have been taken respectively from the work of Dhiren M Joshi and Shih (Shih and Shih 2019 Bottom wall displacement at I input = 0.60 W/cm 2 diluted in ethanol with a concentration of 100 μg/mL) on a holey carbon copper grid and dried overnight.…”
Section: Synthesis Functionalization and Preliminary Characterization...mentioning
confidence: 99%